UNCOVER: The Rest-ultraviolet to Near-infrared Multiwavelength Structures and Dust Distributions of Submillimeter-detected Galaxies in A2744 - Sedona H. Price; Katherine A. Suess; Christina C. Williams; Rachel Bezanson; Gourav Khullar; Erica J. Nelson; Bingjie Wang; John R. Weaver; Seiji Fujimoto; Vasily Kokorev; Jenny E. Greene; Gabriel Brammer; et al. (The Astrophysical Journal)
With the wavelength coverage, sensitivity, and high spatial resolution of JWST, it is now possible to peer through the dust attenuation to probe the rest-frame near-infrared (NIR) and stellar structures of extremely dusty galaxies at cosmic noon ( z  ∼ 1−3). In this paper we leverage the combined Atacama Large Millimeter/submillimeter Array (ALMA) and JWST/Hubble Space Telescope coverage in A2744 to study the multiwavelength (0.5−4.4 μ m) structures of 11 submillimeter detected galaxies at z  ∼ 0.9−3.5 that are fainter than bright “classical” submillimeter galaxies, seven of which are detected in deep X-ray data. While these objects reveal a diversity of structures and sizes, all are smaller and more concentrated toward longer wavelengths. Of the X-ray-detected objects, only two show evidence for appreciable active galactic nucleus (AGN) flux contributions (at ≳2 μ m). Excluding the two AGN-dominated objects, the smaller long-wavelength sizes indicate that their rest-frame NIR light profiles, inferred to trace their stellar mass profiles, are more compact than their optical profiles. The submillimeter detections and visible dust lanes suggest that centrally concentrated dust is a key driver of the observed color gradients. Further, we find that more concentrated galaxies tend to have lower size ratios (rest-frame NIR to optical); this suggests that the galaxies with the most compact light distributions also have the most concentrated dust. The 1.2 mm flux densities and size ratios of these nine objects suggest that both total dust quantity and geometry impact these galaxies’ multiwavelength structures. Upcoming higher-resolution 1.2 mm ALMA imaging will facilitate joint spatially resolved analysis and will directly test the dust distributions within this representative submillimeter population.